Teknologi Mesin Roasting Berbasis Kontrol Suhu Guna Tingkatkan Kualitas dan Produktifitas UMKM Kopi Gupait - Hary Suswanto; Sujito, Sujito; Budi Wibowotomo; Nuzul Zaeni Eki Ramadhanu; Abdullah Iskandar Syah (Rengganis Jurnal Pengabdian Masyarakat, 2025)
MSMEs are the driving force of the community's economy and play an important role in the coffee processing sector. Gupait MSMEs still face obstacles in the roasting process, which is done manually using a hand crank, resulting in unstable temperatures and inconsistent roasting quality. This community service program was implemented using the Participatory Action Research (PAR) method through the stages of observation, socialization, design of a temperature-controlled roasting machine, trial assistance, and operational training for partners. The roasting machine developed has a capacity of 5 kg per roasting process and uses an automatic Temperature Control system. The implementation results showed a significant improvement in the quality of the roasting, with a uniformity level of around 85-90% and no burnt coffee beans, based on visual evaluation from field trials. Additionally, production capacity increased from approximately 1 kg to 5 kg (maximum drum capacity). The assistance also improved partners' understanding of equipment use and maintenance. This program had a positive impact on product quality improvement, process efficiency, and the competitiveness of Gupait MSMEs.